2017
DOI: 10.1080/14767058.2017.1293026
|View full text |Cite
|
Sign up to set email alerts
|

Does implementing a regime of dexamethasone before planned cesarean section at term reduce admission with respiratory morbidity to neonatal intensive care unit? A randomized controlled trial

Abstract: Dexamethasone administration before planned CS at term, as compared to routine management without antenatal steroids, was not associated with a statistically significant reduction in the incidence of admission to NICU with respiratory morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
3
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
1
6
3
3
Order By: Relevance
“…Stutchfield et al 22 reported a lower overall rate of IPPV and endotracheal intubation, but they also did not observe a statistical significant difference between de ACS exposed and not exposed group. Regarding the occurrence of RDS this study also revealed similar rates to those described in the literature, [19][20][21][22] and similar to Nada et al 20 and Nooh et al, 21 we also did not observe a statistically significant difference between the ACS-exposed and not exposed groups. In our study, there was no statistically significant difference between the groups regarding the incidence of TTN, as opposed to what was observed in the randomized cohort studies available in the literature, where the incidence of TTN was lower in the ACS exposed group, with a statistically significant difference.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Stutchfield et al 22 reported a lower overall rate of IPPV and endotracheal intubation, but they also did not observe a statistical significant difference between de ACS exposed and not exposed group. Regarding the occurrence of RDS this study also revealed similar rates to those described in the literature, [19][20][21][22] and similar to Nada et al 20 and Nooh et al, 21 we also did not observe a statistically significant difference between the ACS-exposed and not exposed groups. In our study, there was no statistically significant difference between the groups regarding the incidence of TTN, as opposed to what was observed in the randomized cohort studies available in the literature, where the incidence of TTN was lower in the ACS exposed group, with a statistically significant difference.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, according to the results of the aforementioned randomized cohort studies, prophylactic ACS appeared to decrease the risk of RDS (risk ratio [RR] ¼ 0.48; 95%CI ¼ 0.27-0.87; 3,817 participants), TTN (RR ¼ 0.43; 95%CI: 0.29-0.65; 3,821 participants), and admission to NICU for morbidity due to respiratory reasons (RR ¼ 0.42; 95%CI: 0.22-0.79; 3 studies; 3,441 participants), or any indication (RR ¼ 0.14; 95%CI: 0.03-0.61; 1 study; 452 participants), and the length of stay in the NICU by 2.70 days (mean difference [MD] -2.70; 95% CI: -2.76--2.64; 2 studies; 32 participants). [19][20][21][22][23] The present study found no statistically significant difference between the exposed and not exposed group regarding the likelihood of newborn RDS, TTN, and NICU admission, and even when adjusting for gestational age and arterial hypertension, the likelihood for the occurrence of the aforementioned outcomes was not statistically different between the exposed and not exposed newborns.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations